Synthesis And Characterization Of Pure-Silica- Zeolite-Beta Membrane - Yeong Yin Fong; Subhash Bhatia (ASEAN Journal on Science and Technology for Development, 2006)
The semiconductor industry needs low dielectric constant (low k-value) materials to more advance microprocessor and chips by reducing the size of the device features. In fabricate this context, a new material with lower k value than conventional silica ( k = 3.9 - 4.2 ) is needed in order to improve the circuit performance. As per the recent International Semiconductor Technology plan, a low-k material with a k = 1.6 will be needed by 2010. The choice of the inorganic zeolite membrane is an attractive option for low k material and suitable for microprocess application. In the present study, a pure silica zeolite beta membrane coated on the non-porous stainless steel support was synthesized using in situ crystallization of a gel with the composition of  SiO2 : 0.6 TEAOH : 0.6 HF : 10.1 H2O. The crystallization was carried in the presence of tetraethylammonium hydroxide TEA(OH) as structure directing agent, fumed silica, HF and deionized water at pH value of 9. The crystallization under hydrothermal conditions at 130oC was carried out for the time period of 14 days. The membrane was characterized by X-Ray Diffraction ( XRD ),  Thermogravimetric Analysis ( TGA ), Nitrogen Adsorption and Scanning Electron Microscope ( SEM ) .  SEM micrographs show highly crystalline, truncated square bipyramidal morphology of pure silica zeolite beta was coated on the non-porous stainless steel support. The membrane dielectric constant, k-value was measured as 2.64 which makes it suitable for the microprocessor applications.